A new species of Leptestheria (Crustacea: Branchiopoda: Spinicaudata) from Western Maharashtra, India - Padhye, Sameer; Ghate, Hemant V. (Zootaxa, 2016)
We describe a new species of Leptestheria from a rock pool in the Western Ghats of Maharashtra, India. This species is distinguished from all other Indian congeners by its distinct telson characters and occipital condyle. We also present a comparative table of useful morphological characters of all described Indian Leptestheria species.